1984
DOI: 10.1128/jcm.20.1.94-98.1984
|View full text |Cite
|
Sign up to set email alerts
|

Virus-specific immunoglobulin G subclasses in herpes simplex and varicella-zoster virus infections

Abstract: The subclass specificities of antiviral immunoglobulin G (IgG) produced in response to herpes simplex and varicella-zoster virus infections were investigated. IgGl and IgG3 with anti-herpes simplex virus activity were seen in patients with primary and reactivated disease, as well as in healthy seropositive subjects and in immunoglobulin preparations. IgG4 was occasionally seen alone or together with IgGl and IgG3 in patients. In varicella, IgG3-specific antiviral antibodies were predominant, whereas in zoster,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
32
0

Year Published

1985
1985
2005
2005

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 105 publications
(35 citation statements)
references
References 9 publications
3
32
0
Order By: Relevance
“…That fact that specific IgM and IgA, which evolve in a similar way [Bjorvain, 19741, are generally absent [Schluederberg, 1965;Heffner and Schluederberg, 19671 or, on the other hand, can infrequently appear at only borderline values, after a secondary antigenic stimulation [Morris et al, 19851, corroborates what was observed in the presumed reinfected patients. Likewise, a significantly higher IgG liIgG 3 ratio in group 1 is consistent with published data concerning other viruses which show that IgG 3-specific antibodies are predominant during the primary infection, whereas during reactivation or reinfection IgG 1 is the dominant subclass [Linde et al, 1983;Sundqvist et al, 1984;Linde, 19851. The conclusion that patients of group 1 are in fact reinfected ones can also be drawn by considering the results obtained with the nucleocapsid-directed IgG 3, reported to vary just as IgM during the primary and secondary infections [Henle et al, 1948;Linde et al, 19871. The avidity of specific IgG increases with time after immunization and between the primary and secondary infections [Eisen and Siskind, 1964;Steiner and Eisen, 1967;Webster, 19681.…”
Section: Discussionsupporting
confidence: 90%
“…That fact that specific IgM and IgA, which evolve in a similar way [Bjorvain, 19741, are generally absent [Schluederberg, 1965;Heffner and Schluederberg, 19671 or, on the other hand, can infrequently appear at only borderline values, after a secondary antigenic stimulation [Morris et al, 19851, corroborates what was observed in the presumed reinfected patients. Likewise, a significantly higher IgG liIgG 3 ratio in group 1 is consistent with published data concerning other viruses which show that IgG 3-specific antibodies are predominant during the primary infection, whereas during reactivation or reinfection IgG 1 is the dominant subclass [Linde et al, 1983;Sundqvist et al, 1984;Linde, 19851. The conclusion that patients of group 1 are in fact reinfected ones can also be drawn by considering the results obtained with the nucleocapsid-directed IgG 3, reported to vary just as IgM during the primary and secondary infections [Henle et al, 1948;Linde et al, 19871. The avidity of specific IgG increases with time after immunization and between the primary and secondary infections [Eisen and Siskind, 1964;Steiner and Eisen, 1967;Webster, 19681.…”
Section: Discussionsupporting
confidence: 90%
“…For HSV, CMV, and VZV IgG ELISA with purified nuclear antigens from the respective viruses cultivated in human fetal lung fibroblasts were used. 11,12 The cutoff for seropositivity was an absorbance of >0.2 at a dilution of 1/100. IgG antibodies against influenza A/H1, A/H3, and influenza B were determined with ELISAs by using recombinant influenza antigens.…”
Section: Viral Infections/serological Methodsmentioning
confidence: 99%
“…Since antibody responses evolve after "normal" chickenpox [Leonard, 1970;Sundqvist et al, 1984;Weigle and Grose, 1984;Asano et al, 1987;Kangro et al, 19911, the patients were divided into two groups according to the interval after the most recent episode of chickenpox. Eleven children were first studied within 8 weeks of a repeat attack of chickenpox (Early Group).…”
Section: Materials and Methods Patient Populationmentioning
confidence: 99%
“…individuals with a past history of this disease, and with prior documentation of VZV-seroreactivity [Ross et al, 1983;Gershon et al, 1984;Gurevich et al, 1990;Junker et al, 19911. The host immune-virus interactions that could lead to this phenomenon are ill-understood, but have significance for immunocompromised patients and recipients of varicella vaccine in whom clinical reinfection may be more frequent [Ljungman et al, 1986;Gershon et al, 19921. Over time after chickenpox, the normal humoral immune response to VZV matures with respect to patterns of antibody responses to individual virus proteins [Weigle and Grose, 19841, immunoglobulin and IgG isotype selection [Sundqvist et al, 1984;Asano et al, 19871 and IgG antibody affinity [Kangro et al, 19911. A number of studies have documented differences in antibody responses developed following primary disease (chickenpox) compared to reactivation or reinfection [Weigle and Grose, 1984;Sundqvist et al, 1984;Asano et al, 1987;Kangro et al, 19911.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation